Outpatient Intravenous Antibiotic Therapy: The Vancouver Hospital experience - Grant Stiver; Amy Wai; Lynne Chase; Luciana Frighetto; Carlo Marra; Peter Jewessen (Canadian Journal of Infectious Diseases)
From June 1, 1995 to December 31, 1997, 334 patients at the Vancouver Hospital and Health Sciences Centre (VHHSC) were referred to and screened for, outpatient intravenous antibiotic therapy. One hundred and ninety were accepted, 107 of whom were cared for under the VHHSC program and 83 of whom were discharged to continue intravenous therapy in their own health region. Thirty-four of 144 patients not accepted for outpatient intravenous therapy, were screened by the Infectious Disease Service and Pharmacy, and were discharged on oral antibiotics. Peripherally inserted central catheters were employed in 61 of 107 (57%) patients, peripheral short catheters in 20 (19%), Hickman lines in 14 (13%), and Port-a-caths in 12 (12%). Ninety-two of 107 patients treated in the VHHSC program completed their course uneventfully with resolution of the infection. The average duration of hospital therapy was 10.9 days versus 23.6 days of outpatient therapy. In 15 patients, home treatment was discontinued because of clinical deterioration: adverse drug reaction (n=2), phlebitis (n=2), unsuitable home environment (n=1), noncompliance (n=1), line-related sepsis (n=1) and death due to unrelated causes (n=1). There were 15 adverse drug reactions overall in the total of 2534 patient-days of therapy over 18 months. Cost analysis showed a cost of 12 cents on the dollar compared with inhospital therapy.